Urban tree profiler for urban park area / Haslina Hashim ... [et al.] - Hashim, Haslina; Ahmad Pugi, Noorsazwan; Abdullah, Suzanah; Che Hashim, Izrahayu; Mohamad, Azlizan Adila; Mohd Mokhtar, Munirah Raden (2022)
Tree management in urban park areas is based on in-site observations to obtain the urban tree information and has thus become challenging because it is time consuming, laborious, and costly at the high density developed area. Urban tree information has been stored in conventional methods like in a thick report and is difficult to retrieve. Furthermore, this tree inventory system is currently in tabular form and can only be visualised for internal use. Therefore, the need to have an urban tree profiler is essential in order to expedite the process of updating the urban tree information for conservation and maintenance purposes in the future. The objective of this project is to visualise the urban tree inventory in a two-dimensional (2D) map and develop the tree editor to be used to update the tree information on the site. The output of this project features two dimensional (2D) interactive maps with detailed information of the urban trees. The methodology for this project involved project planning, collection of secondary data, database and interactive map development using geographical information system (GIS), and the smart interface for urban tree visualisations using Google Map. This project enables users to retrieve the details of urban trees and update the tree information from time to time and this tree profiler can be used while on site observation. This project will assist the local authorities and decision makers by providing an efficient solution to the maintenance problem of trees in urban park areas.